MHD free convection-radiation interaction in a porous medium - Part II: soret/dufour effects - Vasu, B.; Gorla, Rama Subba Reddy; Murthy, P.V.S.N.; Prasad, Ramachandra V.; Bég, Anwar O.; Siddiqa, Sadia (Zielona Góra: Uniwersytet Zielonogórski)
This paper is focused on the study of two dimensional steady magnetohydrodynamics heat and mass transfer by laminar free convection from a radiative horizontal circular cylinder in a non-Darcy porous medium by taking into account of the Soret/Dufour effects. The boundary layer equations, which are parabolic in nature, are normalized into non-similar form and then solved numerically with the well-tested, efficient, implicit, stable Keller-Box finite-difference scheme.
Keywords: non-Darcy porous media transport; magnetic field; horizontal circular cylinder; Soret number; Dufour number